2022
DOI: 10.1177/02841851221091209
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic CT in addition to MRI to differentiate between rectal and sigmoid cancer on imaging using the sigmoid take-off as a landmark

Abstract: Background The sigmoid take-off (STO) is a recently established landmark to discern rectal from sigmoid cancer on imaging. STO-assessment can be challenging on magnetic resonance imaging (MRI) due to varying axial planes. Purpose To establish the benefit of using computed tomography (CT; with consistent axial planes), in addition to MRI, to anatomically classify rectal versus sigmoid cancer using the STO. Material and Methods A senior and junior radiologist retrospectively classified 40 patients with rectal/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, this was not possible due to the current daily workload in our department. A recent study found the diagnostic confidence of younger radiologists increased significantly by adding CT to the MRI in the evaluation of the sigmoid takeoff [ 17 ]. Furthermore, we consider it a strength that all included patients had histopathological confirmed adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not possible due to the current daily workload in our department. A recent study found the diagnostic confidence of younger radiologists increased significantly by adding CT to the MRI in the evaluation of the sigmoid takeoff [ 17 ]. Furthermore, we consider it a strength that all included patients had histopathological confirmed adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%